2013
DOI: 10.1371/journal.pone.0052611
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Metabolism and Electrophysiology of Amino Acid and Glucose Stimulated Insulin Secretion: In Vitro Validation Using a β-Cell Line

Abstract: We integrated biological experimental data with mathematical modelling to gain insights into the role played by L-alanine in amino acid-stimulated insulin secretion (AASIS) and in D-glucose-stimulated insulin secretion (GSIS), details important to the understanding of complex β-cell metabolic coupling relationships. We present an ordinary differential equations (ODEs) based simplified kinetic model of core metabolic processes leading to ATP production (glycolysis, TCA cycle, L-alanine-specific reactions, respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 61 publications
3
29
2
1
Order By: Relevance
“…We have consistently shown that alanine is consumed by b-cell lines and islet cells and increases insulin secretion (Dixon et al 2003, Newsholme et al 2010, Salvucci et al 2013, findings that are supported by observations from other b-cell lines including murine and human (Dunne et al 1990, McCluskey et al 2011, Kasabri et al 2012). More recently, we have created an integrated mathematical model which predicted that increased intracellular ATP and Ca 2C levels were critical for glucose plus amino acid-stimulated insulin secretion in BRIN-BD11 cells (Salvucci et al 2013). Furthermore, additional analyses demonstrated that alanine-mediated Na C co-transport acted synergistically with membrane depolarisation and led to K C ATP -independent Ca 2C influx (McClenaghan et al 1998, Salvucci et al 2013.…”
Section: Amino Acid Metabolism and Insulin Secretionsupporting
confidence: 66%
See 2 more Smart Citations
“…We have consistently shown that alanine is consumed by b-cell lines and islet cells and increases insulin secretion (Dixon et al 2003, Newsholme et al 2010, Salvucci et al 2013, findings that are supported by observations from other b-cell lines including murine and human (Dunne et al 1990, McCluskey et al 2011, Kasabri et al 2012). More recently, we have created an integrated mathematical model which predicted that increased intracellular ATP and Ca 2C levels were critical for glucose plus amino acid-stimulated insulin secretion in BRIN-BD11 cells (Salvucci et al 2013). Furthermore, additional analyses demonstrated that alanine-mediated Na C co-transport acted synergistically with membrane depolarisation and led to K C ATP -independent Ca 2C influx (McClenaghan et al 1998, Salvucci et al 2013.…”
Section: Amino Acid Metabolism and Insulin Secretionsupporting
confidence: 66%
“…Furthermore, additional analyses demonstrated that alanine-mediated Na C co-transport acted synergistically with membrane depolarisation and led to K C ATP -independent Ca 2C influx (McClenaghan et al 1998, Salvucci et al 2013. However, the mechanism of action of alanine-induced insulin secretion is multifactorial and includes conversion to pyruvate (Salvucci et al 2013), glutamate, aspartate and lactate ( Fig. 1; Newsholme et al 2010).…”
Section: Amino Acid Metabolism and Insulin Secretionmentioning
confidence: 98%
See 1 more Smart Citation
“…Trinh et al [24] developed and applied the elementary mode analysis as a tool for metabolic pathway analysis in the study of cell physiology and as a basis of metabolic engineering. Salvucci et al [26] integrated biological experimental data with mathematical modelling for the study of regulation of insulin secretion by amino acids and glucose in pancreatic β-cells. In a different approach, other researchers applied mathematical models to gain insights into regulation of metabolic pathways.…”
Section: Eric Arthur Newsholme's Studies: the Basis Of Regulation In mentioning
confidence: 99%
“…Glucose homeostasis requires of insulin secretion, which is mainly regulated by blood glucose. Other compounds such as amino acids may also regulate insulin secretion (Salvucci, Neufeld, & Newsholme, 2013). The stimulating action of amino acids can be attributed to the generation of ATP, direct membrane depolarization (L-arginine and L-lysine) and membrane depolarization through co-transport of Na+ (Liu, Jeppesen, Gregersen, Chen, & Hermansen, 2008).…”
Section: Insulin Secretion By Ins-1e Cellsmentioning
confidence: 99%